DYNAMIC ANALYSIS OF FOUNDATION SUBJECTED TO MACHINE INDUCED VIBRATIONS - Prof. E. Saibaba Reddy, Dr. P. Raja Sekhar, Eadala Rakesh Reddy, B. Haritha Reddy (International Journal of Advanced Science and Technology, 2020)
Machine foundations require a special consideration because they transmit dynamic loads to soil in addition to static loads due to weight of foundation, machine and accessories. The amplitude of vibration of a machine at its operating frequency is the most important parameter to be determined in designing a machine foundation, in addition to the natural frequency of a machine foundation soil system. In this paper, three different case studies are considered, each with different constraints on the operating frequency, dimension of the foundation and dynamic properties of the supporting soil. This paper explores the advantages of using Finite Element analysis in addition to classical tables and analytical solutions, to analysis and design foundations subjected to machine induced vibrations.